Models and emerging trends of concurrent constraint programming - Olarte, Carlos; Rueda, Camilo; Valencia, Frank D. (Constraints : an international journal, 2013)
Concurrent Constraint Programming (CCP) has been used over the last two decades as an elegant and expressive model for concurrent systems. It models systems of agents communicating by posting and querying partial information, represented as constraints over the variables of the system. This covers a vast variety of systems as those arising in biological phenomena, reactive systems, net-centric computing and the advent of social networks and cloud computing. In this paper we survey the main applications, developments and current trends of CCP.